ADVANCED EXPERIENCES OF FOREIGN COUNTRIES IN USING CIRCULAR ECONOMY PRINCIPLES IN SERVICE ENTERPRISES (Marketing Journal, 2026)
This article analyzes the application of the circular economy in service enterprises, especially in the HoReCa (hotel, restaurant, cafe) and hotel -tourism sectors, and its economic and environmental efficiency based on the best practices of foreign countries. The study examines practical approaches of enterprises in Finland, the USA, Brazil, the Maldives and other countries, including waste reduction, efficient use of energy and water resources, use of renewable energy sources, cooperation and monitoring systems. Enterprises that have implemented the circular economy have achieved a reduction in waste by 30–40%, and energy and water consumption by 20–25%. The study shows that the circular economy plays an important role not only in protecting the environment, but also in increasing the competitiveness of enterprises and reducing costs. Foreign experience confirms that the application of the circular economy in the service sector creates opportunities for increasing economic efficiency, saving resources and reducing environmental impact. These approaches are of practical importance for Uzbek service enterprises, and their implementation can lead to sustainable development and increased resource efficiency.
Keywords: circular economy; service enterprises; HoReCa; waste reduction; energy saving; sustainable development; foreign experiences. № 1 -SON YANVA R; 202 6-YIL 49